The structure of Bryant’s empathy index for children: a cross-validation study - Lasa Aristu, Amaia; Holgado Tello, Francisco Pablo; Carrasco Ortiz, Miguel Ángel; Barrio Gándara, María Victoria Del (The Spanish Journal of Psychology, 2008)
The present study examined the structure of Bryant’s Empathy Index (BEI) using different samples for conducting exploratory and confirmatory analyses. The BEI was administered to a sample of 2,714 children (mean age 11.12, SD = 1.59). Exploratory and confirmatory factor analyses showed a three-factor structure: Feelings of Sadness, Understanding Feelings and Tearful Reaction. The results revealed both the multidimensionality of the instrument and appropriate fit indices for the model proposed. Although these results were very similar to those reported in other studies with a Spanish population, the analyses were conducted in a more robust way: with a larger sample and using polychoric correlations and cross validation estimation.